FEN1 is a prognostic biomarker for ER+ breast cancer and associated with tamoxifen resistance through the ERα/cyclin D1/Rb axis - Xu, Lu (Ann Transl Med, 2021)
BACKGROUND: Tamoxifen is an important choice in endocrine therapy for patients with oestrogen receptor-positive (ER+) breast cancer, and disease progression-associated resistance to tamoxifen therapy is still challenging. Flap endonuclease-1 (FEN1) is used as a prognostic biomarker and is considered to participate in proliferation, migration, and drug resistance in multiple cancers, especially breast cancer, but the prognostic function of FEN1 in ER+ breast cancer, and whether FEN1 is related to tamoxifen resistance or not, remain to be explored. METHODS: On-line database Kaplan-Meier (KM) plotter, GEO datasets, and immunohistochemistry were used to analyse the prognostic value of FEN1 in ER+ breast cancer from mRNA and protein levels. Cell viability assay and colony formation assays showed the response of tamoxifen in MCF-7 and T47D cells. Microarray data with FEN1 siRNA versus control group in MCF-7 cells were analysed by Gene Set Enrichment Analysis (GSEA). The protein levels downstream of FEN1 were detected by western blot assay. RESULTS: ER+ breast cancer patients who received tamoxifen for adjuvant endocrine therapy with poor prognosis showed a high expression of FEN1. MCF-7 and T47D appeared resistant to tamoxifen after FEN1 over-expression and increased sensitivity to tamoxifen after FEN1 knockdown. Importantly, FEN1 over-expression could activate tamoxifen resistance through the ERα/cyclin D1/Rb axis. CONCLUSIONS: As a biomarker of tamoxifen effectiveness, FEN1 participates in tamoxifen resistance through ERα/cyclin D1/Rb axis. In the future, reversing tamoxifen resistance by knocking-down FEN1 or by way of action as a small molecular inhibitor of FEN1 warrants further investigation.